1979
DOI: 10.1002/jrs.1250080603
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman spectrum of crystal violet

Abstract: The preresonance Raman spectra, taken under various conditions, of crystal violet have been obtained using the exciting lines of an Ar+ laser. The analysis of the Raman data and of the IR and UV visible absorption spectra allowed us to determine the structure of the ion (propeller-like in shape with D3 symmetry), to characterize the unstable single protonated dye cation, and to propose a detailed vibrational assignment in terms of coupled vibrations of the substituted benzenes. In addition, the measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
85
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 10 publications
(1 reference statement)
12
85
0
Order By: Relevance
“…A recent resonance Raman These bands are not due to aggregation which has study suggests that CV exists as a single D, species been observed in more concentrated solution (3). in solution (5). Magnetic circular dichroism studies The presence of the two overlapping absorption are also consistent with a single propeller-like bands can be due to a single species with a sym-species (either with symmetrical or unsymmetrical metry less than D, (giving rise to two non-angles of twist of the phenyl group) with splitting of degenerate states) or due to two species.…”
Section: Introductionsupporting
confidence: 59%
“…A recent resonance Raman These bands are not due to aggregation which has study suggests that CV exists as a single D, species been observed in more concentrated solution (3). in solution (5). Magnetic circular dichroism studies The presence of the two overlapping absorption are also consistent with a single propeller-like bands can be due to a single species with a sym-species (either with symmetrical or unsymmetrical metry less than D, (giving rise to two non-angles of twist of the phenyl group) with splitting of degenerate states) or due to two species.…”
Section: Introductionsupporting
confidence: 59%
“…It is known that the 9 and ͑ -N͒ modes can couple with the S 0 → S 1 transition through the central carbon-phenyl displacement, and the benzenelike 8 mode is enhanced by the S 0 → S 2 transition. 26,27 Presumably, the observed difference is related to such contributions of different electronic excited states.…”
Section: Fig 2 ͑A͒mentioning
confidence: 99%
“…26 The vibrational modes of free crystal violet ion with propellerlike D 3 symmetry were calculated with B3LYP/ 6-311G ** , which were classified into A 1 ͑Raman active͒, A 2 ͑IR active͒, and E ͑IR/Raman active͒ symmetries. The three HRS peaks belong to the E symmetry.…”
Section: Fig 2 ͑A͒mentioning
confidence: 99%
See 1 more Smart Citation
“…Resonance am& spectroscopy, due to its ability to give detailed molecular information at very low concentration of the sample, is being increasingly used to investigate systems with chromophoric moieties. Spectra of CV have been reported previously (8)(9)(10)(11)(12)(13)(14). All of these communications deal with the normal crystal violet and there is no published report on the resonance Raman spectrum of any of its deuterated derivatives according to the information available to us.…”
Section: Introductionmentioning
confidence: 99%